Some Morphological Studies on the White Rat's liver After birth - Said, Mosbah AbdEl-Gawoad; El-Durssi, Ibrahim S. H.; Gheth, Ebtesam M. M.; Aboalhaj, Abdusalam M. (Al-Mukhtar Journal of Sciences, 2008)
The liver of the rat is situated in the right cranial part of the abdominal cavity closely contact to the abdominal surface of the diaphragm. It is divided into 5 lobes by the interlobar fissures. The Lobus hepatic dexter lateralis is smaller than the Lobus hepatic dexter medialis, the Lobus quadratus is situated between the Lobus dexter medialis and the Lobus sinister. The undivided Lobus sinister is the largest hepatic lobe which has deeply concaved visceral surface where the stomach lies in contact with it forming gastric impression. The Lobus Supraportalis is composed of a Processus caudatus on the right side and Processus papillaris on the left. The Porta hepatic is appeared as a depression between the Processus caudatus and the right part of Processus papillaris where the portal vein, hepatic artery and bile ducts are present